Omani EFL Teachers Engagement in Action Research: Challenges & Opportunities - Al-Balushi, Khadija (Advances in Social Sciences Research Journal, 2022)
Action research engages practitioners in rigorous cycles of planning, observation, action and reflection, which can lead to change in understandings and practice; so, they become reflective practitioners. Despite the importance of action research in informing classroom practice, the literature has shown that there are many challenges that hinder teachers from performing classroom research. This qualitative research study investigated Omani EFL teachers' experiences of participating in classroom action research and the challenges they face in doing research. Data were collected using semi-structured interviews with EFL teachers. 22 participants have been interviewed, out of whom were 18 English teachers and 4 Senior English teachers from 4 public schools in Oman. The findings revealed that some respondents participated in action research activities either as part of their pre-service teacher preparation programmes or through joining in-service action research courses after becoming practitioner teachers. However, they described their action research experience as difficult. The findings highlighted a number of challenges that hinder EFL teachers in Oman from doing action research such as, lack of knowledge, lack of time and lack of interest. The findings suggest that educational policy makers in Oman should create a research culture in schools, and provide incentives for teachers who participate in research activities. Moreover, there is a need to provide EFL teachers with the needed training on research so they become equipped with the knowledge and skills in doing research to improve the quality of teaching and learning in schools and create a community of teacher-researchers in Oman.